Legal and ethical implications of voluntary non-therapeutic sterilization as a way of realization of human reproductive rights - Del Sordo, Sara; Chesnokova, Ekaterina A.; Genovese, Umberto R.; Akulin, Igor M.; Stoyko, Nikolay G. (Вестник Санкт-Петербургского университета. Право, 2019)
This article deals with legal and ethical aspects of sterilization of capable women of reproductive age. The authors point to the ethical and legal contradiction of establishing a high age criterium. Also, the authors consider the most common reasons for litigation during voluntary sterilization.